2021
DOI: 10.1093/infdis/jiab496
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Endometrial Ascension and Enhanced Reinfection Associated With Immunoglobulin G Antibodies to Specific Chlamydia trachomatis Proteins in Women at Risk for Chlamydia

Abstract: Background Previous research revealed antibodies targeting Chlamydia trachomatis (CT) elementary bodies was not associated with reduced endometrial or incident infection in CT-exposed women. However, data on the role of CT protein-specific antibodies in protection are limited. Methods A whole-proteome CT array screening serum pools from CT-exposed women identified 121 immunoprevalent proteins. Individual sera were probed usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 32 publications
1
9
0
Order By: Relevance
“…Data from 222 women, 144 infected and 78 uninfected, were used in this study. The sociodemographic characteristics of participants have been described previously ( 13 ). Women in this study were young (median age, 21 years; range, 18 to 35 years), and the majority of them were single, were African American, and were high school graduates or had some college education.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Data from 222 women, 144 infected and 78 uninfected, were used in this study. The sociodemographic characteristics of participants have been described previously ( 13 ). Women in this study were young (median age, 21 years; range, 18 to 35 years), and the majority of them were single, were African American, and were high school graduates or had some college education.…”
Section: Resultsmentioning
confidence: 99%
“…Among women without Ct infection at enrollment, 9 (18%) were F/U+ and 42 (82%) were F/U−. Seropositivity profiles of 121 Ct protein-specific serum IgGs ( 13 ), previously identified clinical risk factors for ascension (oral contraceptives and gonorrhea), and incident infection (gonorrhea, age, cervical infection at enrollment, and sex with new, uncircumcised, or infected partners) ( 12 ) were subjected to biomarker analysis.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In about 50% of women (1), infection can ascend from the cervix to the upper genital tract (uterus and fallopian tubes), potentially resulting in pelvic inflammatory disease (PID) and leading to devastating long-term sequela including chronic pelvic pain and infertility (2). In previous studies we have identified behavioral, biological, blood transcriptional, cervical cytokine, and Ct antigen-specific T cell and antibody responses, associated with altered risk of endometrial Ct infection (1,(3)(4)(5)(6). However, a major research gap that remains is the lack of biomarker(s) that can identify women at elevated risk of disease.…”
Section: Introductionmentioning
confidence: 99%